Nowe technologie i kryzys demokracji liberalnej w perspektywie teorii aktora-sieci (Politeja, 2025)
NEW TECHNOLOGIES AND THE CRISIS OF LIBERAL DEMOCRACY FROM THE PERSPECTIVE OF ACTOR-NETWORK THEORYThere are two different perspectives in political science regarding the assessment of the impact of technology. On democracy: on the one hand, it is seen as a potential enhancement of pro-democratic processes, while on the other, it is identified as a destructive factor. Regardless of the approach adopted in the analysis of this phenomenon it is necessary to take into account changes in the sphere of social and political communication. The article synthesises interpretations of the democratic backsliding’s origins, considering problems such as disinformation, polarisation of public debate, and changes in the content of politics by digital technologies. At the same time, the use of actor-network theory (ANT) is indicated as a research tool to analyse the crisis, with an emphasis on the dynamic interactions between human and non-human political actors. The article seeks to identify new forms of political subjectivity, to understand the mechanisms of power in the digital age. Moreover, it aims to show how actor-network theory can contribute to a better understanding of the processes of the democratic systems’ (in)adaptation in the face of contemporary technological challenges.